Aerospace 2005
DOI: 10.1115/imece2005-82203
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Design of Vascular Plates

Abstract: Inspired by actuation mechanisms in plant structures and motivated by recent advances in electro-chemically driven micro-pumps, this paper is concerned with a novel concept for active materials based on distributed hydraulic actuation. Due to the similarity of the actuation principles seen in plants undergoing nastic motion, we refer to this class of active materials as nastic materials. We present a mechanical modeling approach for nastic materials representing the effects of pressure generation and fluid tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Especially, the study by Bruhn et al concluded that plant tissues are near-ideal osmotic pressure generators because they are composed of many small motor cells (capsules) with large surface to volume ratio and stiff cell wall reinforcements. To obtain a more efficient overall design, Dunn et al developed a multi-scale optimization scheme, which could optimize the design of cellular material with osmotic actuation at two different hierarchy levels [93]. At the macro-level, this approach optimizes the spatial distribution of the active, shape change components; and at the micro-level, it optimizes the distribution of the fluidic channels for a desired Eigen strain.…”
Section: Passive Pressure Generationmentioning
confidence: 99%
“…Especially, the study by Bruhn et al concluded that plant tissues are near-ideal osmotic pressure generators because they are composed of many small motor cells (capsules) with large surface to volume ratio and stiff cell wall reinforcements. To obtain a more efficient overall design, Dunn et al developed a multi-scale optimization scheme, which could optimize the design of cellular material with osmotic actuation at two different hierarchy levels [93]. At the macro-level, this approach optimizes the spatial distribution of the active, shape change components; and at the micro-level, it optimizes the distribution of the fluidic channels for a desired Eigen strain.…”
Section: Passive Pressure Generationmentioning
confidence: 99%
“…Potential cell topologies are limited to pentagonal and hexagonal cells as they maximize the inherent degrees of freedom, provide a smooth outer surface and minimize the total cell side length for a given cross sectional area. It is therefore rather surprising that some authors approach the design of pressurized cellular structures with the help of topology optimization [184,303]. Despite a predetermined topology, it is still of utmost importance that their geometry is described as efficiently as possible to simplify their simulation and optimization.…”
Section: Geometric Modelmentioning
confidence: 99%